Hematological and biochemical blood indices of rainbow trout depending on the level of protein in feeds - Kondratyuk, V. M. (НУБіП України, 2021)
The article considers the influence of compound feeds with different protein levels on hematological and biochemical parameters of trout blood. The purpose of the experiment was to establish the effect of different protein nutrition levels in commercial rainbow trout feeding on hematological and biochemical parameters of their blood.
Гематологічні та біохімічні показники крові райдужної форелі залежно від рівня протеїну у комбікормах
У статті досліджено вплив використання повнораціонних комбікормів із різним рівнем протеїну на гематологічні та біохімічні показники крові форелі. Метою досліду передбачалося встановити вплив різних рівнів протеїнового живлення товарної райдужної форелі на гематологічні та біохімічні показники їхньої крові.
Keywords: commercial rainbow trout; fish feeding; compound feeds; protein; hematological parameters; leukocyte formula; blood biochemical indices; товарна райдужна форель; годівля риб; комбікорми; протеїн; гематологічні показники